Use of E-Filing System: Antecedents and Consequences to MSME Tax Compliance (International Journal of Scientific Research and Management (IJSRM), 2025)
The study aimed to analyze the effect of Information Quality, System quality, service quality, and the use of e-filing systems on MSME tax compliance. The study population was 128 samples of MSME actors in the Gianyar regency—Analysis technique using the structural equation modeling (SEM) approach with the help of the PLS program. The results of the study show that the overall evaluation of the model is seen from the side of R-Square (R2), Q-Square Predictive Relevance (Q2), and Goodness of Fit (GoF), then the model is declared Good. The results found that the quality of information and the quality of the system have a significant positive effect on the use of the e-filing system, and the use of the e-filing system has a significant positive impact on MSME tax compliance. At the same time, the quality of Service does not affect the use of the e-filing system.